Leveraging IoT technologies for smart hive management and sustainable beekeeping - Stojanova, Simona (Elektrotehniški vestnik, 2025)
Precision beekeeping (PB) integrates digital tools into apiculture to optimize hive management, improve productivity, and enhance sustainability. The study explores the implementation of the Internet of Things (IoT) technologies in beekeeping. It presents a case study within the CODECS Horizon Europe project 1. The case study which is related to beekeepers managing apiaries in remote locations highlights the need for remote monitoring systems. The key technological solutions include automated IoT-supported hive scales, refractometers for measuring the honey moisture content, and conductometers for assessing the honey conductivity. These tools enhance the economic, environmental, and social sustainability by reducing the labor, optimizing the honey production, and minimizing the carbon emissions from unnecessary travels. Results indicate that digital monitoring improves decision-making, reduces colony losses, and supports a data-driven approach to beekeeping, thus promoting sustainable agricultural practices.
Keywords: apiculture; apikultura; beekeeping; čebelarstvo; digitalisation; digitalizacija; IoT sensors; precision agriculture (PA); precizno kmetijstvo; senzorji interneta stvari; sustainability; trajnost